Structural brain changes with lifetime trauma and re-experiencing symptoms is 5-HTTLPR genotype-dependent. Issue 1 (31st December 2020) - Ancelin, Marie-Laure; Carriere, Isabelle; Artero, Sylvaine; Maller, Jerome J; Meslin, Chantal; Dupuy, Anne-Marie; Ritchie, Karen; Ryan, Joanne; Chaudieu, Isabelle
ABSTRACT: Background : Findings on structural brain alterations following trauma are inconsistent due probably to heterogeneity in imaging studies and population, clinical presentations, genetic vulnerability, and selection of controls. This study examines whether trauma and re-experiencing symptoms are associated with specific alterations in grey matter volumes and if this varies according to 5-HTTLPR genotype. Methods : Structural MRI was used to acquire anatomical scans from 377 community-dwelling older adults. Quantitative regional estimates of 22 subregional volumes were derived using FreeSurfer software. Lifetime trauma was assessed using the validated Watson's PTSD inventory, which evaluates the most severe trauma experienced according to DSM criteria. Analyses adjusted for age, sex, total brain volume, head injury, and comorbidities. Results : Of the 212 participants reporting lifetime trauma, 35.4% reported re-experiencing symptoms and for 1.9%, this was severe enough to meet criteria for full threshold PTSD. In participants with the SS 5-HTTLPR genotype only, re-experiencing symptoms were associated with smaller volumes in middle and superior temporal, frontal (lateral orbital, rostral and caudal middle) and parietal (precuneus, inferior and superior) regions. The trauma-exposed participants without re-experiencing symptoms were not significantly different from the non-trauma-exposed participants except for smaller precuneus and superior parietal region in traumatized participants and a larger amygdala in traumatized women specifically. Conclusions : In the non-clinical sample, lifetime trauma and re-experiencing symptoms were associated with smaller volume in prefrontal, temporal and parietal cortex subregions, and this varied according to serotonergic genetic vulnerability, 5-HTTLPR SS individuals being most susceptible.